Stelsels met breuken

Hoofdmenu Eentje per keer 

Substitutie of combinatie

  1. \(\left\{\begin{matrix}-4y=\frac{104}{33}-3x\\-2x-y=\frac{92}{33}\end{matrix}\right.\)
  2. \(\left\{\begin{matrix}-x-y=\frac{-19}{30}\\6x-6y=\frac{91}{5}\end{matrix}\right.\)
  3. \(\left\{\begin{matrix}-2x-y=\frac{14}{3}\\4x-5y=\frac{14}{3}\end{matrix}\right.\)
  4. \(\left\{\begin{matrix}-4x+6y=\frac{226}{15}\\-x=-3y+\frac{221}{30}\end{matrix}\right.\)
  5. \(\left\{\begin{matrix}5x-4y=\frac{-82}{19}\\-2x-y=\frac{268}{95}\end{matrix}\right.\)
  6. \(\left\{\begin{matrix}-5x-6y=\frac{-53}{5}\\4x=y+\frac{46}{15}\end{matrix}\right.\)
  7. \(\left\{\begin{matrix}-5x+3y=\frac{696}{209}\\-5x-y=\frac{-672}{209}\end{matrix}\right.\)
  8. \(\left\{\begin{matrix}-4x+3y=\frac{773}{60}\\4x=y+\frac{-791}{60}\end{matrix}\right.\)
  9. \(\left\{\begin{matrix}-4x-5y=\frac{-313}{13}\\x=-2y+\frac{127}{13}\end{matrix}\right.\)
  10. \(\left\{\begin{matrix}-x+6y=\frac{523}{15}\\-4x=2y+\frac{-248}{15}\end{matrix}\right.\)
  11. \(\left\{\begin{matrix}-2x+4y=\frac{326}{35}\\-x=-6y+\frac{223}{35}\end{matrix}\right.\)
  12. \(\left\{\begin{matrix}5x-5y=\frac{370}{17}\\-x=2y+\frac{130}{17}\end{matrix}\right.\)

Substitutie of combinatie

Verbetersleutel

  1. \(\left\{\begin{matrix}-4y=\frac{104}{33}-3x\\-2x-y=\frac{92}{33}\end{matrix}\right.\qquad V=\{(\frac{-8}{11},\frac{-4}{3})\}\)
  2. \(\left\{\begin{matrix}-x-y=\frac{-19}{30}\\6x-6y=\frac{91}{5}\end{matrix}\right.\qquad V=\{(\frac{11}{6},\frac{-6}{5})\}\)
  3. \(\left\{\begin{matrix}-2x-y=\frac{14}{3}\\4x-5y=\frac{14}{3}\end{matrix}\right.\qquad V=\{(\frac{-4}{3},-2)\}\)
  4. \(\left\{\begin{matrix}-4x+6y=\frac{226}{15}\\-x=-3y+\frac{221}{30}\end{matrix}\right.\qquad V=\{(\frac{-1}{6},\frac{12}{5})\}\)
  5. \(\left\{\begin{matrix}5x-4y=\frac{-82}{19}\\-2x-y=\frac{268}{95}\end{matrix}\right.\qquad V=\{(\frac{-6}{5},\frac{-8}{19})\}\)
  6. \(\left\{\begin{matrix}-5x-6y=\frac{-53}{5}\\4x=y+\frac{46}{15}\end{matrix}\right.\qquad V=\{(1,\frac{14}{15})\}\)
  7. \(\left\{\begin{matrix}-5x+3y=\frac{696}{209}\\-5x-y=\frac{-672}{209}\end{matrix}\right.\qquad V=\{(\frac{6}{19},\frac{18}{11})\}\)
  8. \(\left\{\begin{matrix}-4x+3y=\frac{773}{60}\\4x=y+\frac{-791}{60}\end{matrix}\right.\qquad V=\{(\frac{-10}{3},\frac{-3}{20})\}\)
  9. \(\left\{\begin{matrix}-4x-5y=\frac{-313}{13}\\x=-2y+\frac{127}{13}\end{matrix}\right.\qquad V=\{(\frac{-3}{13},5)\}\)
  10. \(\left\{\begin{matrix}-x+6y=\frac{523}{15}\\-4x=2y+\frac{-248}{15}\end{matrix}\right.\qquad V=\{(\frac{17}{15},6)\}\)
  11. \(\left\{\begin{matrix}-2x+4y=\frac{326}{35}\\-x=-6y+\frac{223}{35}\end{matrix}\right.\qquad V=\{(\frac{-19}{5},\frac{3}{7})\}\)
  12. \(\left\{\begin{matrix}5x-5y=\frac{370}{17}\\-x=2y+\frac{130}{17}\end{matrix}\right.\qquad V=\{(\frac{6}{17},-4)\}\)
Oefeningengenerator vanhoeckes.be/wiskunde 2022-08-18 12:08:26